Activity system, schizotypal personality, and mentalization: A study between halted activity and COVID-19 conducted in Henan, China - El Maouch, Mohamad; Wang, Yile; Jin, Zheng; Tamunang Tamutana, Timothy; Zhao, Kaibin; Liu, Yu (Frontiers in Public Health, 2022)
The pandemic-related lifestyle has potentially imposed crucial disturbances on daily and long-term activities, which, in turn, were associated with thought disturbance. This study investigates how the characteristics of the activity system during pandemic-related restrictions are associated with other psychomental aspects. By focusing on PTSD, mentalization, and schizotypal personality, and by inquiring about the main components of the activity system of 852 college students (Zhengzhou, Henan, China)- including the goals orienting their activity, goals' terms and types, the motivation levels and sources, the activity type and engagement time, the flow of the activity, and how due to pandemic lifestyle-results revealed that the activity system's components have significant associations with PTSD, reflective function, and schizotypal traits. Additionally, some of the activity system's elements have a significant predictive role regarding schizotypal traits. The study considered that the life narrative during the pandemic has been disturbed; hence, this may have a crucial effect on mind coherence. Additionally, the outcomes from the pandemic context will support mental health interventions in other similar contexts where the life narrative is severely affected.